A Descriptive Study on Pregnant Women's Knowledge of the Benefits of Antenatal Care at TK.IV.01.07.02 Binjai Hospital in 2025 - Mardiani Purba (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Antenatal care (ANC) is a planned program involving observation, education, and medical management for pregnant women, aimed at ensuring a safe and satisfying pregnancy and childbirth process. A preliminary survey conducted by the researcher at TK.IV.01.07.02 Binjai Hospital in 2025 involved interviews with 30 pregnant women. Among them, 26 reported attending ANC regularly, while 4 did not, citing a lack of knowledge about ANC as the primary reason. This study employed a quantitative descriptive-analytic survey design, with data presented univariately in narrative form. The results indicate that the majority of respondents 26 out of 30 (86.7%) had good knowledge regarding the benefits of ANC, while only 4 respondents (13.3%) exhibited poor knowledge. Further analysis based on demographic characteristics revealed that most participants were aged between 21–35 years (56.7%), while younger (<20 years) and older (>35 years) women each accounted for 23.3% of the sample. In terms of education, the largest proportion of respondents had completed junior high school (50.0%), followed by senior high school and higher education (each 23.3%), and a small minority had only completed primary school (3.3%). With respect to employment, the majority of respondents (60.0%) were employed, while 40.0% were unemployed. These findings highlight the importance of knowledge in determining ANC utilization among pregnant women and suggest that educational and occupational status may significantly influence health-seeking behaviors during pregnancy.